2020
DOI: 10.1016/j.jcjd.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Care Plan Is Positively Associated With Better Clinical Outcomes in the Care of Patients With Type 2 Diabetes: A Cross-Sectional Real-Life Study

Abstract: Running head Personalized care plan study Key message A personalized care plan is a promising tool to improve cardiovascular risk factors and clinical outcomes of type 2 diabetes patients in the real world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…The impact of the care plan was found to be greater with more care plan rounds, more frequent patient contacts with health care, and if there was continuity with the same physician in the care plan process. In a Finnish cross-sectional study, a personalized care plan was positively associated with better clinical outcomes in type 2 diabetes patients such that patients who had a copy of their care plan were significantly more likely to achieve the systolic blood pressure target and low-density lipoprotein target and to use statins [12]. Our study did not find any significant changes of HRQOL.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The impact of the care plan was found to be greater with more care plan rounds, more frequent patient contacts with health care, and if there was continuity with the same physician in the care plan process. In a Finnish cross-sectional study, a personalized care plan was positively associated with better clinical outcomes in type 2 diabetes patients such that patients who had a copy of their care plan were significantly more likely to achieve the systolic blood pressure target and low-density lipoprotein target and to use statins [12]. Our study did not find any significant changes of HRQOL.…”
Section: Discussioncontrasting
confidence: 46%
“…Although various care plans have been used in Finland and elsewhere for decades, there is still little research on their effectiveness [8,[10][11][12][13][14][15]. Earlier Finnish care plan projects have reported a decrease in the number of health care visits in the long run and improvements in blood lipid levels, blood pressure levels and body mass index (BMI) [12,16,17].…”
Section: Backroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes personalized goal setting and an action plan for treatment. 2 Although legislative frameworks encourage the preparation of care plans for patients with chronic disease, 5,6 only 3.3% of primary care patients in Great Britain 5 and 16% of T2D patients in Finland 7 have been reported to have a care plan in place. Limited availability of resources and other factors may prevent the implementation and utilization of care plans in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In a study among primary care T2D patients, those who had a care plan were observed to have better control in sBP and LDL, and were more likely to use statins than T2D patients without a care plan. 7 The present study aimed to evaluate the clinical outcomes (HbA1c, LDL, blood pressure [BP], and BMI) among T2D patients before, and during 14 months of follow-up after the commissioning of a care plan established according to national care plan instructions in a primary health care setting. The proportion of patients who achieved the recommended treatment targets for blood glucose and cardiovascular risk factors at baseline and follow-up were also examined.…”
Section: Introductionmentioning
confidence: 99%